Characteristics of PEMA/PVdF-HFP blend polymeric gel films incorporated with lithium triflate salt in electrochromic device - Sim, L.N.; Majid, Siti Rohana; Arof, Abdul Kariem (Elsevier, 2012)
Poly(ethyl methacrylate), PEMA and poly(vinylidenefluoride-co-hexafluoropropylene), PVdF-HFP have been blended in the weight ratio 70:30. The blend has been incorporated with lithium trifluoromethanesulfonate (LiCF3SO3) and added with ethylene carbonate (EC) and propylene carbonate (PC). The sample 70 wt.% PEMA/PVdF-HFP - 30 wt.% LiCF3SO3 exhibits the highest room temperature ionic conductivity of 2.87 x 10(-7) S cm(-1) for the blend-salt system. The sample in the PC system (designated 6PC) has the highest room temperature conductivity of 1.46 x 10(-6) S cm(-1). The highest conducting EC system has conductivity of 1.05 x 10(-4) S cm(-1) and the sample is designated as 6EC. The polymeric gel electrolytes are transparent and mechanically stable at room temperature. An electrochromic device (ECD) with configuration glass/FTO/WO3/sample/CeO2-TiO2/FTO/glass utilizing S30, 6PC and 6EC as electrolytes have been fabricated. The cyclic voltammogram (CV) of glass/FTO/WO3/6EC/CeO2-TiO2/FTO/glass shows a cathodic peak occurring at -1.3 V upon coloration while an anodic peak is observed at -0.8 V during bleaching process. (c) 2011 Elsevier B.V. All rights reserved.